Sharia Compliance and Economic Stability: Insights from Bank Syariah Indonesia, Padang Ulak Karang Branch - Amalia, Rizky; Riesmiyantiningtias, Ninuk (Takaza Innovatix Labs Ltd., 2025)
This research examines the impact of Sharia principles on economic stability, focusing on Bank Syariah Indonesia KCP Padang Ulak Karang. Utilizing a quantitative research design, data were collected from 35 employees through total sampling and analyzed using Smart PLS. The study identifies Sharia compliance and risk management as independent variables, with financial performance serving as an intervening variable, and economic stability as the dependent variable. The results indicate that both Prohibition of Riba and Profit and Loss Sharing System significantly influence Sharia compliance, which positively affects financial performance and economic stability. Furthermore, operational risk contributes significantly to risk management, enhancing financial performance and, subsequently, economic stability. Conversely, liquidity risk was found to have no significant effect on financial performance through risk management. These findings highlight the importance of Sharia compliance and effective risk management practices in promoting financial performance and ensuring economic stability within the Islamic banking sector. The study offers insights for banking practitioners and policymakers aiming to foster sustainable growth in the Islamic finance industry.